Chest wall lipoblastomatosis in a 2-year-old girl: a case report and literature review - Yiğiter, Murat; Otgün, Ibrahim; Kiyici, Halil; Akkoyun, Ibrahim; Yücesan, Selçuk; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2010)
Lipoblastoma is an uncommon tumor of adipose tissue that usually occurs in infancy and early childhood. They predominantly locate in the extremities, but are less frequently found in the head and neck region, trunk and various other locations. The most common sign is a rapidly growing mass. In spite of their potential for local invasion and rapid growth, they are benign tumors and have no distant metastasis. Although more than 180 cases of lipoblastoma distributed over various parts of the body have been reported, only nine cases were located in the thoracic wall. We present the case of a two-year-old girl with lipoblastomatosis of the chest wall that was identified by histologic examination. In this article, the English literature on this disorder is briefly reviewed.